2019
DOI: 10.17113/ftb.57.04.19.6369
|View full text |Cite
|
Sign up to set email alerts
|

Aronia Berry Processing by Spray Drying

Abstract: The main aim of this study is to analyze the solid-liquid extraction followed by spray drying as a technological pathway for utilization of aronia fruit dust, a byproduct of filter tea factory. In the current study, ultrasound-assisted extraction was applied for the production of aronia liquid feed and maltodextrin was used as a carrier and encapsulating agent. In spray drying, the influence of inlet temperature and maltodextrin type and mass fraction on process efficiency and powder properties were observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…WSI values were between ranges of 63.34–87.04% ( Table 4 ). These values are similar to those obtained by Navarro-Flores et al [ 35 ] for the encapsulation of Crotalaria longirostrata leaves, and higher than those obtained by Vidović et al [ 36 ] for the encapsulation of aronia fruit dust (average of 57.2%), but lower than WSI obtained for white horehound powder (92.19%) [ 37 ]. By comparing the WAIs of the powders, it can be inferred that the microcapsules prepared with WP had significantly higher adsorption in comparison to MD, with the highest being in 80% WP powder, indicating that it is more likely to be affected by humidity and less stable during storage.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…WSI values were between ranges of 63.34–87.04% ( Table 4 ). These values are similar to those obtained by Navarro-Flores et al [ 35 ] for the encapsulation of Crotalaria longirostrata leaves, and higher than those obtained by Vidović et al [ 36 ] for the encapsulation of aronia fruit dust (average of 57.2%), but lower than WSI obtained for white horehound powder (92.19%) [ 37 ]. By comparing the WAIs of the powders, it can be inferred that the microcapsules prepared with WP had significantly higher adsorption in comparison to MD, with the highest being in 80% WP powder, indicating that it is more likely to be affected by humidity and less stable during storage.…”
Section: Resultssupporting
confidence: 89%
“…This indicates that MD powders could be easily and effectively reconstituted in water, easily incorporated, and evenly distributed into products. An increase of WSI with an increase of MD mass fraction was also reported in the study by Vidović et al [ 36 ] for spray drying of aronia fruit dust.…”
Section: Resultssupporting
confidence: 79%
“…This was related to the increase in drying speed at higher temperatures. Additionally, this trend was also confirmed by other studies on spray drying chokeberry juice [ 8 , 9 , 17 ] and other berries [ 22 , 23 , 24 , 25 , 26 , 27 ]. However, in the study by Bednarska and Janiszewska-Turak [ 12 ], no statistical significance was found for the effect of drying temperature on the moisture content of spray-dried chokeberry juice.…”
Section: Resultssupporting
confidence: 81%
“…It was assumed that at 180 °C (as in the case of spray drying of chokeberry juice), a substantial effect on the powder sticking would decrease PY value. Vidović et al [ 17 ] also noted a maximum PY in spray drying of chokeberry juice, but at a lower temperature (T = 140 °C). However, it was not a semi-industrial process, but only conducted on a laboratory scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation